Interdisciplinary multimodality management of stage III nonsmall cell lung cancer. (8th July 2019) - Huber, Rudolf M.; De Ruysscher, Dirk; Hoffmann, Hans; Reu, Simone; Tufman, Amanda
Stage III nonsmall cell lung cancer (NSCLC) comprises about one-third of NSCLC patients and is very heterogeneous with varying and mostly poor prognosis. It is also called "locoregionally or locally advanced disease". Due to its heterogeneity a general schematic management approach is not appropriate. Usually a combination of local therapy (surgery or radiotherapy, depending on functional, technical and oncological operability) with systemic platinum-based doublet chemotherapy and, recently, followed by immune therapy is used. A more aggressive approach of triple agent chemotherapy or two local therapies (surgery and radiotherapy, except for specific indications) has no benefit for overall survival. Until now tumour stage and the general condition of the patient are the most relevant prognostic factors. Characterising the tumour molecularly and immunologically may lead to a more personalised and effective approach. At the moment, after an exact staging and functional evaluation, an interdisciplinary discussion amongst the tumour board is warranted and offers the best management strategy. Stage III NSCLC is a heterogenous group. Outcome depends on a good inter- and multidisciplinary strategy. Local treatment and systemic therapy both have to be optimised. Interdisciplinary trials integrate systemic targeted therapy or immunotherapy. bit.ly/2WstXtX